Total phenolic contents and free-radical scavenging activities of grape (Vitis vinifera L.) and grape products - Keser, Serhat; Celik, Sait; Turkoglu, Semra (Taylor & Francis Ltd, 2013)
Grape is one of the world's largest fruit crops, with an approximate annual production of 58 million metric tons, and it is well known that the grape skins, seeds and stems, waste products generated during wine and grape juice processing, are rich sources of polyphenols. It contains flavonoids, phenolic acids and stilbenes. In this study, we tried to determine antioxidant properties and phenolic contents of grape and grape products (fresh fruit, seed, dried fruit, molasses, pestil, vinegar) of ethanol and water extracts. Antioxidant properties of extracts were investigated by DPPH center dot, ABTS(center dot+), superoxide, H2O2 scavenging, reducing power, metal chelating activity and determination of total phenolic contents. The seed extracts revealed highest ABTS(center dot+), DPPH center dot, H2O2 scavenging and reducing power activities. Furthermore, these extracts showed higher total phenolic contents than other grape product extracts.
Keywords: ABTS(center dot+); grape; grape products; DPPH center dot; superoxide; H2O2; total phenolic